Study of Curcumin and Bisdemethoxycurcumin from Curcuma longa L. on Neutrophils in G6PD Defi ciency - Sanmun, Duangmanee; Changtam, Chatchawan; Prasartkaew, Salinrat; Nanti, Ajchareeya; Khamkorkaew, Kanitta (Journal of Health Science of Thailand, 2017)
Curcuma longa L. has been widely used as spice in tropical countries. The turmeric extract of rhizomes is composed of the active compounds called curcuminoids. Curcuminoids consist of curcumin (CUR), demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC), which are natural antioxi dants. This study aimed to determine the efficacy of curcumin and bisdemethoxycurcumin and their roles on neutrophil phagocytosis in normal and G6PD-deficient subjects. Curcumin and bisdemethoxycurcumin were used to stimulate the function of neutrophils by nitroblue tetrazolium (NBT) test under the light microscope, and then the positive cells were counted and converted to percentage of neutrophils reducing NBT. Study in males with G6PD deficiency found that phagocytic activity of neutrophils in either curcumin or bisdemethoxycurcumin stimulation at 3 µM was greater than control activation by phorbol 12-myristate 13-acetate (PMA). In addition, when neutrophils were co-stimulated with PMA along with curcumin, the NBT reduction was significantly higher than in PMA stimulation alone (p<0.05). These results suggest that turmeric extracts perhaps increase neutrophil function as indicated above.